Imaging topological radar technology as a general purpose instrument for remote colorimetric assessment, structural security, cataloguing, and dissemination. (August 2015) - Guarneri, Massimiliano; De Dominicis, Luigi; Ferri De Collibus, Mario; Fornetti, Giorgio; Francucci, Massimo; Nuvoli, Marcello; Danielis, Alessandro; Mencattini, Arianna
Abstract : While today 3D digitisation techniques are commonly applied in several areas of cultural heritage, introducing new ways for monitoring, cataloguing, and studying masterpieces, the use of these technologies is not always worthwhile in terms of costs/benefits. The ENEA UTAPRAD-DIM laboratory has developed opto-electronic devices for cultural heritage applications. Two different 3D laser scanners for terrestrial and underwater inspection have been the subject of laboratory research for the last decade and a new technique known as imaging topological radar (ITR) has been developed and patented. The ITR system is based on the superimposition of three amplitude-modulated laser sources for the simultaneous acquisition of data related to colour and structure. This approach opens new scenarios for colour measurement and remote/non-invasive analysis, reducing the gap between costs and benefits from the technology. Several factors affect the quality of data collected by ITR, such as the precision of the scanner mechanism, the material and shape of the work studied, and the geometry of scanning (i.e. distance and angular dependencies). This paper explores the effect of the geometry of scanning on point cloud quality, focussing attention on data correction algorithms and their practical application. The data collected during the digitisation of the Sistine Chapel using the RGB-ITR scanner serve as a case study for validating the theoretical assumptions, models, and algorithms.